Prevention and Control of Infectious Diseases Act 1988 [Act 342] Prevention and Control of Infectious Diseases (Measures within the Infected Local Areas) Regulations 2020 (P.U.(A) 91/2020) - Ali Mohamed, Ashgar Ali; , (LexisNexis, 2020)
The right of every person to move freely throughout the Federation and to reside in any part thereof is guaranteed by the Federal Constitution article 9(2). However, clause 3 of article 9 conferred power on the Parliament to enact law imposing restrictions in respect of movement and residence on grounds related to public order, public health, or the punishment of offenders. Hence, pursuant to art 9(3) and by virtue of section 11(2) of the Prevention and Control of InfectiousDiseases Act 1988, the Prevention and Control of Infectious Diseases(Measures Within The Infected Local Areas) Regulations 2020 were enacted and came into effect from 18 March 2020 to 31 March 2020, which has now been extended to 28 April 2020.